Lymphatic vessel density as a prognostic indicator in Asian NSCLC patients: a meta-analysis - Shuanglan Xu; Jiao Yang; Shuangyan Xu; Yun Zhu; Chunfang Zhang; Liqiong Liu; Hao Liu; Yunlong Dong; Zhaowei Teng; Xiqian Xing (BMC Pulmonary Medicine, 2018)
Abstract Background To determine the association of lymphatic vessel density (LVD) with the prognosis of Asian non-small cell lung cancer (NSCLC) patients via a meta-analysis. Methods Eligible studies were selected by searching PubMed and EMBASE from inception to July 25, 2017. The reference lists of the retrieved articles were also consulted. The information was independently screened by two authors. When heterogeneity was significant, a random-effects model was used to determine overall pooled risk estimates. Results A total of 15 studies with 1075 patients were finally included in the meta-analysis. LVD was positively associated with the prognosis of NSCLC in the overall analysis (hazard ratio (HR) 1.14, 95% confidence interval (95% CI): 1.02–1.27, p = 0.000, I2 = 73.2%). Subgroup analyses were performed on 5 VEGFR-3 groups (p = 0.709, I2 = 0.0%), 3 LYVE-1 groups (p = 0.01, I2 = 86.4%), 5 D2–40 groups (p = 0.019, I2 = 66.2%), and 2 podoplanin groups (p = 0.094, I2 = 64.5%). Sensitivity analysis indicated robust results. There was no publication bias. Conclusions LVD is an indicator of poor prognosis in Asian NSCLC patients.